2015
DOI: 10.1590/bjpt-rbf.2014.0089
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of hip muscle strengthening in patellofemoral pain syndrome patients: a systematic review

Abstract: Introduction: Patellofemoral pain syndrome (PFPS) is characterized by anterior knee pain, which may limit the performance of functional activities. The influence of hip joint motion on the development of this syndrome has already been documented in the literature. In this regard, studies have investigated the effectiveness of hip muscle strengthening in patients with PFPS.Objectives:The aims of this systematic review were (1) to summarize the literature related to the effects of hip muscle strengthening on pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 23 publications
2
34
0
6
Order By: Relevance
“…Although most of the trials failed to report the session duration, they provided similar session frequencies (mean ± SD, 3.5 ± 1.4 per week) and program durations (mean ± SD, 6.0 ± 2.5 weeks). In addition, this systematic review included 4 recent randomized trials since the last review was published, 39 and also investigated whether the benefits of intervention are maintained beyond the intervention period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although most of the trials failed to report the session duration, they provided similar session frequencies (mean ± SD, 3.5 ± 1.4 per week) and program durations (mean ± SD, 6.0 ± 2.5 weeks). In addition, this systematic review included 4 recent randomized trials since the last review was published, 39 and also investigated whether the benefits of intervention are maintained beyond the intervention period.…”
Section: Discussionmentioning
confidence: 99%
“…4,37,39,44 The first review suggested that hip strengthening had a positive effect on pain reduction, with effect sizes ranging from 0.54 to 0.62. 4 The second review found that the addition of hip strengthening decreased pain during activity (mean difference, -2.2; 95% confidence interval [CI]: -3.8, -0.6) and usual pain (mean difference, -1.8; 95% CI: -2.8, -0.8), but did not change functional ability (standardized mean difference [SMD], 0.6; 95% CI: -0.4, 1.6) in comparison to knee strengthening alone.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They found no between‐group differences in pain and function despite superior gains in muscle strength for the exercise group, and superior gains in step rate for the gait retraining group. That clinical improvements are not necessarily tied to improvements in muscle strength is observed in two previous systematic reviews . This may suggest that clinical improvements may be moderated by factors other than muscle strength.…”
Section: Discussionmentioning
confidence: 87%